Prophet of judgement day an exposition of the prophecy of Joel - Tatford, Frederick Albert, 1901- (Sussex, UK Prophetic Witness, 1974)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Joel -- commenttaries